Data analytics on consumer behavior in omni-channel retail banking, card and payment services - GENG DAN (Institutional Knowledge at Singapore Management University, 2016)
Innovations in financial services have created challenges for banks that Information Systems (IS) research can address. My interests involve transaction cost theory, substitution and complementarity theory, and consumer informedness theory to understand consumer behavior and firm performance in the omni-channel world of digital banking. At a high level, my research inquiry asks: How can financial institutions take advantage of the deep insights that data analytics and management science modeling create on consumer behavior and channel management decision-making? And how can changes in payments and services in retail banking be understood in spatial and temporal terms? I am working on three essays. They involve theoretical arguments and data analytics related to physical branch network, omni-channel behavior and credit card analytics in retail banking services. Essay 1 investigates branch network and omni-channel customer banking behavior. Essay 2 examines the impact of credit card partnerships between banks and retailers. Essay 3 applies spatiotemporal econometrics and data mining to explore the penetration of Bitcoin. Through sponsored research access to unique data from banks in U.S. and Singapore, and assistance from industry professionals, I will contribute new knowledge on consumer insights related the inner workings of financial services and technology.